Degradasi Zat Warna Rhodamin-B Menggunakan Green Fotokatalis Seng Ferit (ZnFe2O4) - Ekstrak Daun Pucuk Idat (Cratoxylum Glaucum) - Sindi Atika Putri; Ike Nur Amanah; Jeni Susilawati; Verry Andre Fabiani (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2021)
Currently the development of the textile industry is not accompanied by proper textile waste treatment. Dyes from the textile industry are simply thrown away, causing dangerous environmental problems. One of the dyes that is often used in the textile and food industry is rhodamine B. An alternative for handling dye contamination is using photocatalyst technology. ZnFe2O4, nanoparticles have photocatalytic activity with UV light and visible light for the degradation of rhodamine B. This study aims to determine the characteristics of zinc ferrite (ZnFe2O4,) using a bioreductant of pucuk idat leaf extract (Cratoxylum glaucum) and determine the percent degradation of rhodamine B dye using zinc ferrite photocatalyst material. – leaf extract of pucuk idat (Cratoxylum glaucum). The method that will be used in this research is the experimental method. Broadly speaking, this research includes the extraction of pucuk idat leaves, synthesis of zinc ferrite-pucuk idat leaves and their characterization. To calculate the % degradation of rhodamine-B, first determine linear regression with variations in concentrations of 5 ppm, 10 ppm, 15 ppm, 20 ppm, and 25 ppm. The regression equation y= 0.0154x–0.0149 and the correlation coefficient (R2) with a linearity of 0.9857 were obtained. After characterization using XRD, FTIR, UV-Vis, and calculations, the highest percentage of rhodamine-B degradation was found in the sample RB + ZnFe2O4 + UV 3 hours, with a % degradation value of 16.42%.